2010
DOI: 10.1096/fj.09-153924
|View full text |Cite
|
Sign up to set email alerts
|

The oligomerization properties of prion protein are restricted to the H2H3 domain

Abstract: The propensity of the prion protein (PrP) to adopt different structures is a clue to its pathological behavior. The determination of the region involved in the PrP(C) to PrP(Sc) conversion is fundamental for the understanding of the mechanisms underlying this process at the molecular level. In this paper, the polymerization of the helical H2H3 domain of ovine PrP (OvPrP) was compared to the full-length construct (using chromatography and light scattering). We show that the oligomerization patterns are identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
76
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 40 publications
19
76
0
Order By: Relevance
“…The fact that the misfolded states M1 and M2 are stabilized in the mutant suggests that they could act as intermediates leading to oligomerization, with the mutation driving increased aggregation via enhanced occupancy of the misfolded intermediates. The existence of different misfolding pathways might possibly relate to the ability of PrP to form different oligomeric structures (46,47), but additional measurements will clearly be needed to establish such a link. Additional studies will also be needed to address the question of how the misfolding of isolated PrP molecules relates to PrP Sc formation, e.g., by exploring the effects of mutations enhancing pathogenicity (48), probing the effects of different pH conditions, and observing aggregate formation directly.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the misfolded states M1 and M2 are stabilized in the mutant suggests that they could act as intermediates leading to oligomerization, with the mutation driving increased aggregation via enhanced occupancy of the misfolded intermediates. The existence of different misfolding pathways might possibly relate to the ability of PrP to form different oligomeric structures (46,47), but additional measurements will clearly be needed to establish such a link. Additional studies will also be needed to address the question of how the misfolding of isolated PrP molecules relates to PrP Sc formation, e.g., by exploring the effects of mutations enhancing pathogenicity (48), probing the effects of different pH conditions, and observing aggregate formation directly.…”
Section: Discussionmentioning
confidence: 99%
“…Although conformational change of the A-state into the ␤-rich oligomer was not clarified in the present study, the following two models were suggested as the initial process based on the A-state conformation (Fig. 6, A and C): (a) refolding of the highly unstable S1-H1-S2 region into a ␤-sheet structure and their subsequent intermolecular interactions (40) and (b) intermolecular interaction between the H2 and H3 regions, where the hydrophobic core is probably exposed to the solvent in the A-state because of the unstable S1-H1-S2 region (32,41,42). Recently, ␤-sheet conversion of residues 118 -122 in the crystal structure of the human prion protein has been observed (43).…”
Section: Discussionmentioning
confidence: 99%
“…32,[41][42][43][44] The β helix 31,32 and the in-register models 44 have in common to propose the existence of a "prion domain" (as in yeast prions) 45 shorter than the whole PK-resistant segment, but they conflictingly locate it to efficient conversion as these amino acids were kept in our initial study, so as to minimize the eventual impacts on the formation of the last helix. Their removal from an otherwise well tolerated insert indeed impaired prion replication ( Table 1, compare lanes 1 and 8 or lanes 5 and 9).…”
Section: Insertions In the H2-h3 Domain And Structural Models Of Prp Scmentioning
confidence: 99%